Response to "The Many Misspellings of Albuquerque: A Comment" - Peter Christensen; Christopher Timmins (Institute for Replication (I4R), 2024)
We thank the authors of this report for their careful re-analysis of our paper, "Sorting or Steering: The Effects of Housing Discrimination on Neighborhood Choice" and the Institute for Replication for supporting this work. In the process of replicating the results published in Christensen and Timmins (2022), Chen et al. raise two concerns and provide an independent set of analyses to address the concerns. In particular, the authors report findings from two changes to the original analysis: (1) regressions that make use of a variant of the 'city' variable that is used throughout the paper as a control, and (2) dropping observations for testers identified as 'other' (not white, LatinX, or Asian). The authors find that several of the coefficients and standard errors reported in the study are sensitive to these changes. They conclude that while significance and magnitude are affected in certain instances, their re-analysis affirms the paper's primary finding of substantial and nuanced housing racial discrimination. This document provides responses to the concerns discussed by Chen et al., additional analysis that addresses the concerns, and a discussion of the implications for the interpretation of findings in Christensen and Timmins (2022). (...)
Keywords: 330